On the Political Nature of Philosophy - Zbrzeźniak, Urszula (Sensus Historiae, 2022)
The purpose of this text is to outline a problem that arose in antiquity and remains relevant today, namely the relationship between philosophy and politics. According to the main thesis, this relationship is inevitable and, although it has taken various historical forms, philosophy cannot avoid referring to the political sphere. In the second part of the text, selected philosophical positions will be examined to identify the form this relationship takes today.